CONVERTED NEOLOGISMS IN JOURNALISM (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article examines the role of conversion as a mechanism of word formation in the creation of neologisms, with a specific focus on journalism. Conversion allows for the rapid adaptation of language to new societal trends, technological advancements, and cultural shifts. Through the process of conversion, journalists contribute to the creation and dissemination of new words, reflecting the evolving nature of communication in the digital age. Examples such as to google, to text, to blog, and to tweet illustrate how the media plays a central role in shaping the lexicon. This paper explores the significance of conversion in linguistic innovation and highlights how journalists facilitate the emergence of new words in response to changing contexts.